The Development of Student Live Worksheets Based on Problem Based Learning in the Optical Instrument Chapter - Hendrayani, Aditya; Permana, Niki Dian; Ilhami, Aldeva; Syarif, Muhammad Ilham (IJIS Edu : Indonesian Journal of Integrated Science Education, 2022)
Solving science problems theoretically is sometimes difficult for students to do. This is because students have never been in directcontact with science problems. This study aims to develop student live worksheets based on problem based learning on opticalinstrument chapter The research method used reffered to the research and development by Sugiyono. This model has stepsconsisting of 10 steps: (1) Potential and problems, (2) Data collection, (3) Product design, (4) Design validation, (5) Designrevision, (6) Product trial, (7) Product Revision, (8) Usage Trial, (9) Product Revision, and (10) Mass production. Thisresearch was only carried out until the seventh step. This study used data collection techniques in the form of interviews andquestionnaires and used qualitative and quantitative descriptive data analysis techniques.The results of the validity of the studentlive worksheet had been declared very valid based on the results of the validation of the learning material experts who obtaineda score of 85% with a very valid category, and media experts obtained a score of 77.08% with a very valid category. In addition,the student work sheet was declared very practical with a value of 97.22% without revision. Based on the students' responses,they scored 91.67% in the very good category. Based on these data, it can be said that the student live worksheet Based onProblem Based Learning on Optical Instrument chapter stated to be very valid and practical to be used as science teachingmaterial in schools